ANALISIS KONTRADIKSI AKTIVITAS PROSTITUSI DI EKS. LOKALISASI PAKEM, BANYUWANGI - Efendi, Irfan; Priyanto, Hary; Pahlevi Hentina, Niko (Fakultas Ilmu Sosial dan Ilmu Politik Universitas 17 Agustus 1945 Banyuwangi, 2025)
Analysis of the contradictions in prostitution activities at the former Pakem localization, Banyuwangi, covers several important points.The main issue lies in the uncertainty of the status of the former localization area that was supposed to be closed, yet there are still covert prostitution activities.This research aims to understand the social dynamics and conflicts that arise due to the presence of prostitution in the area.The research methodology uses a qualitative approach with purposive sampling and snowball sampling techniques to determine informants.Data collection was carried out through interviews, observations, and documentation.The research results show that although the government has made efforts to close down former localization areas, prostitution activities continue, causing dissatisfaction among the community.The discussion reveals that this contradiction creates social conflict between the community that rejects the existence of prostitution and those who consider it a source of income.The government's performance in enforcing regional regulations is also considered less effective, causing the community to feel unprotected.The conclusion of this research emphasizes the need for decisive action from the government to permanently close former localization areas and enhance collaboration between the government, law enforcement, and the community to create a safer and more orderly environment.